What causes reduced tax morality and how can it be improved? - Nteleza, Tinna Snenjongo (Department of Finance and Tax, 2022)
There has been a notable decline in the tax morality of South African taxpayers over the years. Tax morality is a term defined as the willingness of individuals to pay tax and comply with tax laws1 . The concerns over the decline in tax morality were raised by the National Treasury when discussing the widening tax gap between the budgeted tax revenue collections and the actual revenue collected (in the 2017 Budget Speech)2 . The importance of tax morality in South Africa cannot be overstated, the very success of South Africa's democracy is dependent on the very functioning of the fiscal citizenship principle, that means the state and the taxpayers must be committed to the operation of the democracy through the social contract, ie the taxpayers must be willing to pay their taxes and the government must provide the services due to the taxpayer, such as healthcare, education services and efficient infrastructure. In the evaluation of South Africa's tax morality, the tax revenue collection process and methodology must be reviewed. For personal income tax, with the exception of PAYE, taxpayers must declare their income earned in order for the income to be assessed. It is for this reason that tax morality should be regularly reviewed, to ensure that taxpayers are motivated to pay the right amount of tax and are compliant with tax laws. Where this is not the case, symptoms of broken fiscal citizenship can include aggressive tax avoidance, base erosion and profit shifting and tax evasion, to an extent that legislation needs to be constantly reviewed in order to protect the South African tax base. To review the tax morality of the Republic, revenue collection statistics such as tax buoyancy are reviewed, revealing that after the 2008/9 global financial crisis, the revenue collection statistics remained buoyant until the 2017/18 period during which time it decreased to 0.91 indicating a threat to the long-term sustainability of the fiscal policy. The tax revenue collections when compared to GDP statistics also signal concern, and when taking into account the rate at which high networth individuals are leaving the country and their reasons, it is clear that the South African government should be applying more focus and resources in improving tax morality. In order to recommend focus areas to improve tax morality, a review of research performed by the OECD globally into the tax morale of individuals and businesses around the world is used. The research focuses on factors influencing tax morale, which is a good indicator of what motivates taxpayers to participate in, and comply with a tax system. An overarching theme for individuals from the identified factors is the perspective of the government taxpayers have. It is this perspective that has been found in the study to influence whether individual taxpayers around the world comply with and participate in the tax laws of the country. For businesses, the most dominant factor appears to be tax certainty and while this is information derived from a general survey and on a limited population, it provides a general overview or a starting point in the improvement of tax morality. With the factors identified, an evaluation of how they impact the South African population and to what extent the findings may be true for the Republic are investigated. The socioeconomic and institutional factors identified in the global study are relatable in the South African context and the results from the survey show parallels between the global population and the South